Comparative Analysis of Financial Performance between Digital Banks and Conventional Banks Registered with Financial Services Authority - Anggraini, Shasa Nur; Abidin, Zaenal (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the comparison of financial performance between Digital Banks and Conventional Banks for the 2021-2023 period. Financial performance is measured based on the indicators Return On Asset (ROA), Return On Equity (ROE), Net Interest Margin (NIM), Operating Costs to Operating Income (OC/OI), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL) and Fee-Based Income Ratio (FBI). The type of research used is quantitative research. The data used in this study is secondary data obtained from the company's annual report from 2021 to 2023. The sample used consisted of 7 Digital Banks and 7 Conventional Banks. The hypothesis testing includes using the Independent Samples t-test and the Mann-Whitney U test. There is a significant difference in the financial performance of Digital Banks and Conventional Banks, specifically in the NIM and NPL ratios. Meanwhile, there is no significant difference in the financial performance between Digital Banks and Conventional Banks for 2021-2023, based on the ROA, ROE, OC/OI, LDR, and FBI ratios.